Pregnancy counseling in rheumatic diseases: Where science meets the steps - Anu Balakrishnan; Pankti Mehta; Latika Gupta (Indian Journal of Rheumatology)
Most rheumatic diseases (RDs) have a predilection for women in the reproductive age group. Common drugs used in rheumatology practice have identified risks to the fetus; thus, adequate pregnancy counseling is of utmost importance. Contraception and adequate preparation for the same can enhance the experience of motherhood and decrease intra as well as peripartum complications. The knowledge, as well as practices of contraception in autoimmune diseases, are low and varied in various populations. The challenges faced in different RDs are unique and keen understanding can be fruitful toward better patient care. A multi-disciplinary team effort between the patient, obstetricians, and the rheumatologist is the key to better maternal and fetal outcomes.